Partitioning of trace elements, As, Ba, Cd, Cr, Cu, Mn and Pb, in a 2.5 MWth pilot-scale circulating fluidised bed combustor burning an anthracite and a bituminous coal - Duan, Lunbo; Sun, Haicheng; Jiang, Ying; Anthony, Edward J.; Zhao, Changsui (Elsevier, 2016)
Coal combustion introduces large amounts of pollutants into the atmosphere, including trace elements originally bonded in the coal matrix. The emission of these elements raises considerable environmental and human health concerns. To optimise process parameters and reduce gaseous trace element emissions, it is of significant importance to investigate the solid–gas partitioning behaviour of trace elements during combustion processes. To date, limited numbers of experimental studies have been carried out, especially using pilot circulating fluidised bed (CFB) combustion plants. This paper discusses the partitioning behaviour of seven elements (As, Ba, Cd, Cr, Cu, Mn and Pb) in different product streams during combustion tests on anthracite and bituminous coal. The combustion tests were carried out in a 2.5 MWth CFB unit equipped with multi-stage control of solids, which is well suited for trace element partitioning studies. The mass balance ratio of the elements studied ranged from 56%–137%, which is, considering their concentrations, both satisfactory and reasonable. Most of the elements were found in the bottom ash and fly ash during CFB combustion, while small amounts of As, Cd and Pb were emitted to the atmosphere along with fine particulates. The trace elements are more likely to be retained in the bottom ash from the bituminous coal but not in the case of anthracite. For the volatile elements, the enrichment in solid streams follows the trend of: bag filter ash > cyclone ash > IBHX (in-bed heat exchanger) solids > bottom ash, indicating that the volatile elements tend to be enriched in fine particles. Anthracite, when compared to bituminous coal, shows lower emission factors for all monitored elements, except for Pb. This study can serve as a good reference for trace element control strategies in coal-fired CFB boilers.
Keywords: Trace elements; Circulating fluidised bed; Mass balance ratio; Enrichment; Emission